Malabsorption of Dietary Folate (Pteroylpolyglutamates) in Adult Coeliac Disease and Dermatitis Herpetiformis. Issue 5727 (10th October 1970) - Hoffbrand, A. V.; Douglas, A. P.; Fry, L.; Stewart, J. S.
Abstract : Tests of absorption of folic acid (pteroylglutamic acid) and of dietary folates (pteroylpolyglutamates) were performed in 10 patients with untreated adult coeliac disease, five with dermatitis herpetiformis, and three with nutritional folate deficiency. Absorption of pteroylglutamic acid was impaired in eight patients with coeliac disease and in two with dermatitis herpetiformis. Absorption of pteroylpolyglutamates was impaired in all 10 coeliac patients and in four of the five patients with dermatitis herpetiformis. Absorption of both forms of folate was normal in all three patients with nutritional folate deficiency.